Conception and Implementation of an IoT System for Remote Practical Works in Open Access University’s Electronic Laboratories - Moulay Taj, Amine; Chacon Sombria, Jesus; Gaga, Ahmed; Abouhilal, Abdelmoula; Malaoui, Abdessamad (International Journal of Online and Biomedical Engineering (iJOE), 2021)
The courses and disciplines in the exact sciences are based on practical work (PW) which complements the theoretical teaching. Remote Labs are a recent approach used for educating experimental manipulations by using the performance of information and communication technologies. This work aims to propose the design of an IoT system allowing several remote manipulations in analog electronics. This solution is mainly based on the Red Pitaya STEMLab board, in particular for communication and remote control for measurements and data acquisition through different protocols. The low-cost system provides an intelligent selection between the different integrated practical works on a developed board, as well as other ones carried out externally as extensions according to the professor’s needs. The analysis of the integrated manipulations was done taking into account the minimum latency of the remote control as well as its portability to save time, space, and money without loss of quality and quantity. The presented results relate to a PW of analog electronics, a “RC charging and discharging circuit” has been considered for a comparison of this Remote system with the same PW performed by the classical method "hands-on laboratory". Our purpose in this study is the development of a control system to maximize the available resource as well as to improve self-learning ability in the electronic field.